Are Pre-Service EFL Teachers Ready for AI-Assisted Assessment? The Role of Assessment Literacy in the Digital Era - Ayuningtryas, Vina; Emaliana, Ive (Institut Agama Islam Negeri Madura, 2025)
Artificial Intelligence (AI) is transforming educational assessment, particularly in English as a Foreign Language (EFL) settings. As the use of AI is becoming increasingly rapid, pre-service teachers must become proficient with both Language Assessment Literacy (LAL) and preparation to utilize AI tools. Therefore, this study explored the relationship between LAL and AI-based assessment readiness among Indonesian EFL pre-service teachers. Adopting a mixed-method explanatory sequential research design, 200 respondents across 60 universities in Indonesia participated through a questionnaire survey followed by interviews with the highest and lowest AI readiness scores. The quantitative data found a significant moderate positive correlation, implying that higher LAL is associated with greater readiness to use AI-based assessment. Moreover, the descriptive data indicated that while most participants demonstrated high LAL, their AI readiness was only moderately high. Qualitative data revealed that the respondents with better LAL have critical views about practices when it comes to assessment. The research concluded that to effectively integrate AI into assessment practices, pre-service teachers not only need technology skills training but also a solid assessment knowledge. These results have implications for the curriculum in teacher education, for which there is demand for integrated frameworks that link assessment theory with ethical AI implementation.